2020
DOI: 10.1016/j.carres.2020.107909
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterisation of two medium molecular mass exopolysaccharides produced by the bacterium Lactobacillus fermentum Lf2

Abstract: Under optimized conditions, the lactic acid bacterium Lactobacillus fermentum Lf2 secretes up to 2 gL-1 of a mixture of polysaccharides into the fermentation medium when grown on sucrose. Earlier studies had shown that the mixture is biologically active and work was undertaken to characterise the polysaccharides. Preparative size exclusion chromatography was used to separate a high molecular mass -glucan (weight average mass of 1.23 x 10 6 gmol-1) from two medium molecular mass polysaccharides (weight average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Taking into account the results of the conducted studies, the probability that endogenous intoxication plays a very significant role in the development of toxicosis, exacerbating the course of the pathological process, is significant. Since the main feature of MMM lies in their ability to further aggravate metabolic disorders that caused their synthesis, forming a kind of vicious circle [11,17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account the results of the conducted studies, the probability that endogenous intoxication plays a very significant role in the development of toxicosis, exacerbating the course of the pathological process, is significant. Since the main feature of MMM lies in their ability to further aggravate metabolic disorders that caused their synthesis, forming a kind of vicious circle [11,17].…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the loss of aromatic amino acids by proteins as a result of oxidative modification and fragmentation of molecules. The most informative is the estimate of the MMM coefficient of 280/254 nm, since an increase in this indicator may indicate an increase in catabolic processes, stimulation of lipid peroxidation and immunogenesis [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the purified EPS extract was mainly composed of a high molecular mass β-glucan (1.23 × 10 6 g mol −1 ) and two medium molecular mass polysaccharides (average weight mass of 8.8 × 10 4 g mol −1 ). The composition of the EPS depended on the culture conditions, since under statistically optimized growth conditions, the medium molecular mass molecules represented more than 75% of the mixture [17], while the high molecular mass β-glucan predominated under non-optimized conditions. Additionally, the β-glucan demonstrated immunomodulatory properties in peripheral blood mononuclear cells, as it modulated proinflammatory mediators (such as TNF-α), suggesting that it may reduce the risk of digestive diseases such as Crohn's disease and ulcerative colitis [18].…”
Section: Introductionmentioning
confidence: 99%
“…This is because LAB fermentation can cause a series of biochemical changes in proteins and carbohydrates while also improving the physicochemical and processing properties of grain foods. In addition, LAB can do much to ameliorate the flavor, texture, shelf life, and nutritional quality of fermented grain foods (Ahmed et al, 2020;Ispirliet al, 2020). Crittenden et al (2001) stated that the Bifidobacterium strain bound to the surface of starch particles had the ability to secrete amylase and metabolize starch.…”
Section: Introductionmentioning
confidence: 99%